2021
DOI: 10.1002/smll.202008182
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous MnV2O6‐Zn Battery with High Operating Voltage and Energy Density

Abstract: Aqueous Zn ion batteries (AZIBs), featuring low cost, long‐term cycling stability, and superior safety are promising for applications in advanced energy storage devices. However, they still suffer from unsatisfactory energy density and operating voltage, which are closely related to cathode materials used. Herein, the use of monoclinic MnV2O6 (MVO) is reported, which can be activated for high‐capacity Zn ions storage by electrochemically oxidizing part of the Mn2+ to Mn3+ or Mn4+ while the remaining Mn2+ ions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…In recent years, some cathode materials (Mn‐ and V‐based materials) with both relatively high capacity and high voltage have been proposed, such as Co 0.247 V 2 O 5 ⋅0.944 H 2 O, [51] MnV 2 O 6 , [14b] and α‐MnO 2 [52] (see Table 3). However, they are still not ideal for ultrahigh‐energy‐density zinc batteries.…”
Section: Design Strategies For High‐capacity and High‐voltage Aqueous...mentioning
confidence: 99%
“…In recent years, some cathode materials (Mn‐ and V‐based materials) with both relatively high capacity and high voltage have been proposed, such as Co 0.247 V 2 O 5 ⋅0.944 H 2 O, [51] MnV 2 O 6 , [14b] and α‐MnO 2 [52] (see Table 3). However, they are still not ideal for ultrahigh‐energy‐density zinc batteries.…”
Section: Design Strategies For High‐capacity and High‐voltage Aqueous...mentioning
confidence: 99%
“…In this regard, it is speculated that the atomiclevel structure engineering can lead to changes in chemical and physical properties, which can improve the energy storage performance and cycling life as well. [36][37][38][39][40][41][42][43][44][45][46][47][48] However, designing MnO 2 cathodes at atomic-level scale with higher power and energy density still holds a huge challenge.…”
Section: Introductionmentioning
confidence: 99%
“…[37,38] A combination of Mn-and V-based oxides is an attractive choice for AZIBs for achieving superior cycling stability and high voltage. [39,40] Yan Wu et al reported the carbon nanotube (CNT)-wrapped MnV 2 O 6 as a cathode for AZ-IBs. The Mn 2+ could act as a pillar/binder to maintain the stable layer structure during the process.…”
Section: Introductionmentioning
confidence: 99%